Modelling Transport in an Interregional General Equilibrium Model with Externalities - Morten Marott Larsen; Bjarne Madsen; Chris Jensen-Butler (European Regional Science Association (ERSA), 2005)
In this working paper the regional impacts of road pricing on cars are analysed taking into account externality effects from transportation on wages and productivity. In the paper the direct impacts from changes in transport costs on level of wages and productivity (=direct externality effects) have been estimated. The direct and derived impacts of road pricing have been analysed with AKF's local economic model LINE and include the impacts on regional production, income and employment. LINE is an interregional general equilibrium model, which uses an interregional social accounting matrix (SAM-K) and a regional transport satellite account as the basis for modelling. Additionally, data from a GIS-system (Technical University of Copenhagen) on transport costs have been included to estimate the demand for transport commodities and increase in transport demand and costs due to road pricing. The direct effects on level of wages and productivity have been included into the model together with all the direct effects on commodity prices from road pricing. In the working paper the total impacts of road pricing have been subdivided into 2 components: 1) The wage effects of reducing income net of commuting of increasing transport cost by introduction of road pricing, 2) the labour contraction effect from increasing wages through increase in commuting cost and 3) the negative productivity effects of introducing road pricing. In total the impacts of road pricing are substantial. Regions with high level of average commuting cost (suburban areas in Greater Copenhagen) suffers most, whereas the centre of Copenhagen suffers least because of short commuting distances. In rural areas impacts are on or just below average because low level of road pricing.
Keywords: 330